Cemeteries and society in Merovingian Gaul : selected studies in history and archaeology, 1992-2009 - Halsall, Guy (Brill's series on the early Middle Ages, 2010)
Seven of Guy Halsall's most important essays on the social interpretation of Merovingian cemetery archaeology are collected in this volume. The opening chapter discusses the relationships between documentary history and archaeology while the subsequent articles cover the interpretation of fourth-century Gallic furnished inhumations, the celebrated burial of King Childeric I, and the ways in which one might 'read' a burial as evidence for ritual. The final part of the book looks at the social history of Merovingian communities as revealed in cemetery evidence, looking at gender, sexuality and age. The reprinted chapters are accompanied by two wholly rewritten pieces and two entirely new articles. Finally, the book contains five extended 'commentaries' on the debates to which these chapters contributed.